Thickener design for a copper concentrate using rheology, sedimentation and compression parameters - Quiero-Gelmi, Aldo; Olcay-Barreda, Rubén; Mamani-Apala, Paola (Wydział Geoinżynierii, Górnictwa i Geologii Politechniki Wrocławskiej, 2024)
This study was carried out to evaluate the operation of the thickener at mine site, in addition to increasing the geometallurgical information of the mining process. It analyzes the results of the sizing of a thickener that treats copper concentrate ore slurry from the flotation process. For this purpose, discon-tinuous sedimentation tests were carried out to determine: the effect of the flocculant dosage on the sedi-mentation velocity, on the sediment in compression, and on the thickener design by Adorjan’s method, which uses sedimentation parameters and compression parameters, and is complemented with rheological parameters obtained from the calculation of the effective solid stress and the measurement of the yield stress in slurries without the addition of flocculant. Batch sedimentation tests were performed for floccu-lant dosage between 0–20 g/TMS and volume fraction concentrations between 0.025–0.130. The results obtained show that the sedimentation velocity tends to constant and maximum values starting at a dose of 4 g/TMS; however, the analysis of the sediment granulometry indicates that the addition of flocculant is not necessary, since there is no significant size segregation for low dosage of flocculant; and finally, the design of the thickener by Adorjan’s method indicates that the optimum value would be 20 g/TMS. When evaluating the rheological parameters for the concentrate without the addition of flocculant, it is observed that the behavior of the effective solids stress and yield stress have a marked increase in their values for volumetric fractions of 0.45 (79.60% of solids by mass), which would indicate a change in the fluidity of the concentrate, so it is correct to design the thickener for a discharge volumetric concentration of 0.239, which corresponds to the range used in the industrial operation, and it is expected that the fluidity of the concentrate thickener discharge will have an adequate rheological behavior.
Mining Science, Vol. 31, 2024, s. 103-118
Keywords: górnictwo; geologia; geoinżynieria; thickener; design; Adorjan; sedimentation; compression; rheology